Parallel Investigation As An Effective Step In Handling Cases Of Money Laundering Crimes Arising From Forestry And Environmental Crimes - Paklioy, Ronny Putra Dirgantara; Sopacua, Margie Gladies (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Parallel Investigation, is a concept in the enforcement of money laundering or money laundering, in Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering or hereinafter referred to as the Anti-Money Laundering Law Article 74 stipulates that